2024
DOI: 10.1039/d3cc04825j
|View full text |Cite
|
Sign up to set email alerts
|

Dealloying-derived nanoporous Sn-doped copper with prior selectivity toward formate for CO2 electrochemical reduction

Hefeng Yuan,
Bohao Kong,
Zhehao Liu
et al.

Abstract: We report nanoporous Cu-Sn catalysts fabricated by chemically dealloying rapidly solidified Al-Cu-Sn alloys for CO2RR. The np-Cu11Sn1 catalyst exhibits a three-dimensional interconnected ligament-channel network structure, which can efficiently convert CO2...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…3(a–c), the rough surface of vertical fracture consists of innumerable nanoparticles and the available interpenetrating ligament channel network structure with an up-and-down connection, the spherical nanoparticles uniformly are precipitated and aggregated on the cross-linked framework surface. 25,33 The related elemental mapping confirms the Cu and O enrichment, as well as the presence of residual internal Al and Zr in Fig. 3(d).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…3(a–c), the rough surface of vertical fracture consists of innumerable nanoparticles and the available interpenetrating ligament channel network structure with an up-and-down connection, the spherical nanoparticles uniformly are precipitated and aggregated on the cross-linked framework surface. 25,33 The related elemental mapping confirms the Cu and O enrichment, as well as the presence of residual internal Al and Zr in Fig. 3(d).…”
Section: Resultssupporting
confidence: 57%
“…Based on the emphasis on the chemical homogeneity and compositional tunability of metallic glasses, the porous metal frameworks interspersed in active substances are constructed by employing chemical or electrochemical corrosion techniques, enabling the large-scale production of integrated catalytic materials. 24–26 Specifically, excess elements with lower electrode potentials will be selectively corroded away, further allowing diffusion and recombination of the residual elements with high catalytic activity and stability. The formation of micro-nanoporous structures is adequately determined by the disordered arrangement of atoms and the diffusion effect of high energy density in metallic glasses.…”
Section: Introductionmentioning
confidence: 99%
“…In chemical dealloying, the HEA-loaded substrate is generally submerged into a chemical solution of either highly corrosive acids or alkali to selectively etch away specific elements in the HEA, particularly aluminum (Al) which is amphoteric in nature, thereby making it susceptible to gentler dealloying using alkaline etchants instead of harsher acids. 116–118 Jin et al 119 demonstrated the dealloying of Al-based AlNiCoIrMo HEA NPs to achieve a resulting 119 nanoporous catalyst for water splitting applications in acidic environments. Using 0.5 M NaOH solution, the Al content in the HEA was selectively removed to realize this nanoporous structure containing ultrafine nanopores and nanoligaments.…”
Section: Novel Synthesis Methods Of Hea Nanocatalystsmentioning
confidence: 99%